How medical students' perceptions of instructor autonomy-support mediate their motivation and psychological well-being. (2nd June 2020) - Neufeld, Adam; Malin, Greg
Abstract: Purpose: Medical student well-being is an increasing concern in medical education. Understanding the role instructors and programs have in supporting well-being is an important puzzle piece. This study explores the relationship between medical students' perceptions of instructor autonomy-support, motivation, and well-being. Using self-determination theory, we aim to provide a practical framework through which medical instructors can support student autonomy and well-being in the learning environment. Materials and methods: Students from the University of Saskatchewan completed a survey measuring perceptions of the learning climate (LC) (instructor autonomy-support), satisfaction/frustration of basic motivational needs (autonomy, competence, relatedness), and psychological well-being. Multiple linear regression was used to determine whether age, gender, and year of study affected students' well-being, before a mediation model was tested to assess the direct effect of the LC and indirect effects of students' basic need fulfillment on their well-being. Results: The response rate was 183/400 (46%). Higher ratings of autonomy-support significantly predicted better student well-being. This was mediated completely by students' feelings of basic need fulfillment. Relatedness satisfaction contributed most to ratings of instructor autonomy-support. Conclusions: Cultivating autonomy-support for medical students is critical to their well-being. Learning environments that optimize autonomy-support will also support students' feelings of relatedness and competence.